Development of graphical user interface (GUI) in determination geomagnetic parameters using MAGDAS data / Mohd Faizul Sudin - Sudin, Mohd Faizul
The accuracy of prediction and monitoring the magnetic variation should be increased. The accuracy can be increased by analyzing the methods that arc used for observation and execution of the raw data. The parameter of magnetic that produces most of the effect on prediction and introduces serious accuracy degradation into the system is Magnetic Data Acquisition System (MAGDAS). By modeling this MAGDAS parameter, the evaluation of the prediction error and the correction of these prediction errors for differential prediction can be done. Thus, the analysis using the single frequency method using the graphical user interface is an easy, simple, more efficient and accurate way of determining and analyzing this MAGDAS parameter.